ChemInform Abstract: Face to Face Activation of a Phenylselenium Borane with α, β‐Unsaturated Carbonyl Substrates: Facile Synthesis of C—Se Bonds. Issue 51 (23rd December 2014) - Sanz, Xavier; Vogels, Christopher M.; Decken, Andreas; Bo, Carles; Westcott, Stephen A.; Fernandez, Elena
Abstract Activated olefins directly react with phenylselenium borane (II) without any metal or organocatalytic assistance.